Outcomes of uveitic cataract surgery in a cohort of South African children - Kennedy, Clare (Division of General Surgery, 2024)
BACKGROUND: Cataract formation is a common and potentially blinding complication of paediatric uveitis. Surgical management approach remains a point of controversy. The purpose of this study was to determine the peri- and postoperative outcomes of uveitic cataract surgery in a cohort of South African children. METHODS: Retrospective case-series of paediatric patients with uveitis who underwent cataract surgery between 01/01/2010 to 31/12/2020. The main outcome measures were postoperative best corrected visual acuity (BCVA), intra- and postoperative complications, and immunosuppressive requirements. RESULTS: The study included 18 eyes from 14 patients. Fifteen eyes underwent a pars plana vitrectomy, lensectomy with capsulectomy and were left aphakic. Three eyes had an anterior approach lensectomy with insertion of a posterior chamber intraocular lens (PCIOL). All eyes had improvement in BCVA, with a mean gain of 5 lines. BCVA equal to or better than 6/12 was achieved in 68.8% of eyes with 62.5% seeing 6/9 or 6/6. The most common post operative complication was cystoid macular oedema (CMO). Of the 3 eyes that had PCIOLs inserted, 2 required removal.